New perspectives on the glymphatic system and the relationship between glymphatic system and neurodegenerative diseases - Yan-rui Sun; Qian-Kun Lv; Jun-Yi Liu; Fen Wang; Chun-Feng Liu (Neurobiology of Disease)
Neurodegenerative diseases (ND) are characterized by the accumulation of aggregated proteins. The glymphatic system, through its rapid exchange mechanisms between cerebrospinal fluid (CSF) and interstitial fluid (ISF), facilitates the movement of metabolic substances within the brain, serving functions akin to those of the peripheral lymphatic system. This emerging waste clearance mechanism offers a novel perspective on the removal of pathological substances in ND. This article elucidates recent discoveries regarding the glymphatic system and updates relevant concepts within its model. It discusses the potential roles of the glymphatic system in ND, including Alzheimer's disease (AD), Parkinson's disease (PD), and multiple system atrophy (MSA), and proposes the glymphatic system as a novel therapeutic target for these conditions.